Enhancement of rolling energy conversion of a boat using an eccentric rotor revolving in a hula-hoop motion. (1st April 2016) - Wang, Yu-Jen; Yu, Jui-Hsin
Abstract: This study developed an energy converter composed of an eccentric rotor and a circular Halbach-array magnetic disk to convert the energy created by the rolling motion of a sailing boat into electrical energy. The proposed eccentric rotor was expected to be capable of converting reciprocating rolling motion into a rotational hula-hoop motion when equipped with an appropriate weighted block. The eccentric rotor revolving in a hula-hoop motion enhances power generation because the angular velocity is higher than that provided by small-amplitude oscillation. The rolling frequencies and angles for hula-hoop motion occurrence correspond with the main frequencies and amplitudes obtained from the spectrum analysis of the rolling-motion signal of a 700-ton sailing boat. Comprehensive dynamic analysis of the proposed energy converter was conducted to characterize the relationships between the various parameters and the probability of hula-hoop motion occurrence. An approximate solution was derived according to the numerical results, and the corresponding stability analysis was evaluated using the homotopy perturbation method and the Floquet theory to create an occurrence criteria map for hula-hoop motion. The magnetic flux density and electromagnetic damping of the circular Halbach-array magnetic disk were evaluated using magnetic field strength simulation and Faraday׳s law of induction. A rolling motion emulator was constructed to verify the performance of the energy converter. The output power of a 6.25-kg prototype connected to an external load of 300 Ω in series was 1.37 mW at a rolling frequency of 0.30 Hz and a rolling angle of 10°. A large version of the proposed energy converter can be applied as a backup power source for a sailing boat, and a small version can be used as a power source for self-powered sensors installed on a boat. Highlights: Eccentric rotor revolving in hula-hoop motion enhances energy conversion of boat. Eccentric rotor with suitable L * revolves in hula-hoop motion in regular rolling. Eccentric rotor with suitable L * enhances power conversion in irregular rolling. Approximate solutions are derived for acquiring the map of hula-hoop motion. Experimental and numerical power generation results are consistent.